The Investigation of QCM-Based VOCS Gas Sensor Sensitivity Using Impedance Analysis - Mokhtar, Nur Raudatusyahirah; Mustafa, Mohd Kamarulzaki Mustafa (Enhanced Knowledge in Sciences and Technology, 2025)
Gas sensors play a crucial role in contemporary environmental surveillance and industrial safety, acting as an important defense against the detrimental impacts of toxic materials, especially Volatile Organic Compounds (VOCs). This study investigates cutting-edge developments in gas sensor technology using the Quartz Crystal Microbalance (QCM) dipping technique. The study improves sensor performance by applying calix[6]arene and 4-tert-Butylcalix[4]arene onto the QCM surface, showcasing its capability for accurate and effective gas detection. Experimental findings show that raising the quantity of chemical deposition layers on the QCM surface greatly enhances its sensitivity, as reflected by variations in impedance peaks. In particular, the impedance peaks diminish with more layers, emphasizing the QCM’s capacity to identify even slight mass variations. Of the VOCs tested, Toluene showed the greatest impedance values, signifying stronger molecular interactions with the QCM surface in comparison to Ethanol and Acetone. This behaviour can be explained by Toluene’s greater molecular size and distinctive chemical characteristics. Additional examination of vapor levels indicated that reduced concentrations lead to increased impedance peaks, highlighting the sensor’s improved sensitivity at low vapor amounts. This trait is especially beneficial for identifying small quantities of dangerous gases in practical situations. To conclude, this study marks an important advancement in gas sensing technology, providing valuable information on the capabilities of QCM-based sensors for various applications. This research establishes a foundation for future advancements in gas detection systems by tackling issues like sensitivity, selectivity, and portability. The results not only advance sensor technology but also emphasize the essential function of QCM-based sensors in protecting public health and the environment.